Cooperative peace in asia / edited by Jasjit Singh - Jasjit Singh (ed.) (New Delhi, 1998)
This book covers the following topics Overall situation in East Asia, including China and Korean peninsula / Tomoyuki Kojima ; Strategic developments in East Asia : an overview / K.N. Ramachandran; Overview of South Asian situations and Japan's policy initiatives towards the region / Kazuya Ogawa ; Emerging trends in southern Asia / Chintamani Mahapatra ; Nuclear issues and Asian security / C. Raja Mohan ; The security situation in Asia / Kunio Takahashi ; Regional cooperation in Asia Pacific / Tsutomu Kikuchi ; India and Asian regional economic groupings / Sanjaya Baru ; India-Japan relations and cooperation: an Indian view / G.V.C. Naidu ; Japan-India relations and cooperation: a Japanese perspective / Sakutaro Tanino ; Strengthening peace in Asia / Jasjit Singh etc.
Keywords: Nuclear - Asia